Neonatal infective endocarditis in a cardiac rhabdomyoma case: A rare presentation (Indian Journal of Case Reports, 2021)
Neonatal infective endocarditis (IE) is an exceedingly rare disease and usually not associated with cardiac rhabdomyomas or any underlying structural cardiac anomalies. Cardiac rhabdomyoma is also the most common benign primary cardiac tumor. The prognosis depends on the size, location of tumors, and outflow tract obstruction but can regress within 2 months of age and reduces the necessity of surgery. Due to the variable clinical features and course, we need to evaluate cardiac vegetation as soon as possible for better outcomes. A combination of these two conditions was not reported before. Here, we presented a case of IE with cardiac rhabdomyoma in a male baby which is first reported from Bangladesh previously.